Enzymology of the beta-ketoadipate pathway in Trichosporon cutaneum. - Powlowski, J B (1985)
Cell extracts were prepared from Trichosporon cutaneum grown with phenol or p-cresol, and activities were assayed for enzymes catalyzing conversion of these two carbon sources into 3-ketoadipate (beta-ketoadipate) and 3-keto-4-methyladipate, respectively. When activities of each enzyme were expressed as a ratio, the rate for methyl-substituted substrate being divided by that for the unsubstituted substrate, it was apparent that p-cresol-grown cells elaborated pairs of enzymes for hydroxylation, dioxygenation, and delactonization. One enzyme of each pair was more active against its methyl-substituted substrate, and the other was more active against its unsubstituted substrate. Column chromatography was used to separate two hydroxylase activities and also 1,2-dioxygenase activities; the catechol 1,2-dioxygenases were further purified to electrophoretic homogeneity. Extracts of phenol-grown cells contained only those enzymes in this group that were more active against unsubstituted substrates. In contrast, whether cells were grown with phenol or p-cresol, only one muconate cycloisomerase (lactonizing enzyme) was elaborated which was more active against 3-methyl-cis,cis-muconate than against cis,cis-muconate; in this respect it differed from a cycloisomerase of another strain of T. cutaneum which has been characterized. The cycloisomerase was purified from both phenol-grown and p-cresol-grown cells, and some characteristics were determined.